2012
DOI: 10.1002/bjs.8877
|View full text |Cite
|
Sign up to set email alerts
|

Oncoplastic surgery for breast cancer based on tumour location and a quadrant-per-quadrant atlas

Abstract: A quadrant-per-quadrant approach to oncoplastic techniques for breast cancer was developed that tailors the mammoplasty for each tumour location. This panel of techniques should be a useful guide for breast surgeons, and extends the possibilities for breast conservation for large or poorly limited cancers, with a low complication rate and good cosmetic results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
114
1
13

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(135 citation statements)
references
References 20 publications
7
114
1
13
Order By: Relevance
“…Standard lumpectomy typically excises less tissue and presumes a seroma cavity which heals through scarring. Standard adjuvant radiation to the lumpectomy site increases scar formation, often leading to poor aesthetic outcomes including nipple retraction and deviation [23]. With LVOS, the lumpectomy cavity is obliterated with tissue rearrangement thus minimizing nipple retraction and skin depression and potentially improving future aesthetics [23].…”
Section: Discussionmentioning
confidence: 99%
“…Standard lumpectomy typically excises less tissue and presumes a seroma cavity which heals through scarring. Standard adjuvant radiation to the lumpectomy site increases scar formation, often leading to poor aesthetic outcomes including nipple retraction and deviation [23]. With LVOS, the lumpectomy cavity is obliterated with tissue rearrangement thus minimizing nipple retraction and skin depression and potentially improving future aesthetics [23].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, to achieve the desired oncological results, this change may play an important role to get good cosmetic outcomes and improve quality of life in patients (1,2). New innovations are created in the mentioned surgical techniques, emphasizing more on the cosmetic results after surgery through the reconstruction of partial mastectomy, called oncoplastic (3)(4)(5). Different studies showed desirable and appropriate therapeutic results for this method such as good cosmetic outcomes, better control over tumor margin, high satisfaction of patients, and high probability of breast conservation (6)(7)(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…Oncologic breast reconstructions can be classified depending on the oncological procedure performed and the timing of breast reconstruction. There is no consensus on either the classification to be used in defects that can occur in breast cancer surgery or the ideal OBS technique to be used for correction of this problem (14,15). Although many authors have made some algorithm suggestions on this subject, most breast center use algorithms based on their own experience.…”
Section: Current Status and Oncologic Breast Reconstructions;mentioning
confidence: 99%
“…The NAC is raised and repositioned in the midline without excision of too much breast and skin tissue. The same process is applied to the contralateral breast for breast symmetry (15,25).…”
Section: A-breast Volume Displacement;mentioning
confidence: 99%
See 1 more Smart Citation